Self-talk of Counsellor Trainees: A Preliminary Report - Uhlemann, Max; Lee, Dong Yul; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
This study addressed the following questions: (a) What is the nature of the internal dialogue of beginning counsellors prior to their initial interview with a client, and (b) What is the relationship between that internal dialogue and counsellor effectiveness? A 50-item self-talk questionnaire was designed to assess the positive and negative self-talk of 73 counsellor trainees prior to their initial client interviews. Practicum supervisors used a 10-item semantic differential scale to evaluate counselling effectiveness. The results showed that counsellor trainees experienced predominantly positive rather than negative self-talk. However, neither the amount of positive or negative sell-talk, nor the proportion of positive to negative self-talk was correlated with counsellor effectiveness. The implications of these findings for counsellor training and research are discussed.